Liberté, volonté, responsabilité : Faust Socin, Gerhard Johannes Vossius et les arminiens de Hollande - Luisa Simonutti (Astérion)
The article of Luisa Simonutti deals with the criticism and the use of some key concepts of Socin (liberty, will, responsibility) by some Dutch Arminians. This complex inheritance is not only a part of the important reaction against the works and the thought of Socin that took place from the end of the Sixteenth Century to the end of the Seventeenth Century. It is also to be interpreted as a moment of the debate for the defence of the libertas prophetandi and of the free will of man in front of the laws and the will of God.